PERLINDUNGAN HAK TERHADAP ANAK PELAKU TINDAK PIDANA BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK DI RUTAN KELAS IIB SIAK SRI INDRAPURA - Evi Ratna Evalinda S; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Children in conflict with the law hereinafter referred to as children are children who are 12 (twelve) years old, but not yet 18 (eighteen) years old who are suspected of committing a criminal act. Children undergoing criminal periods and children sentenced to imprisonment are placed in LPKA. There are still children who are placed in detention centers or state detention centers that should be places of detention for adults, besides that children's rights are seized by people who should provide protection both physically and mentally. The purpose of this thesis, namely; first, the protection of the rights of the offender in the Class IIB Detention Center for Siak Sri Indrapura, secondly, the obstacle in protecting the rights of the offender in the Class IIB Detention Center of Siak Sri Indrapura, thirdly, the efforts taken to overcome the obstacles in protection the right to the child of the offender in the Class IIB Detention House of Siak Sri Indrapura. The type of research used in this study is sociological legal research. Sociological legal research is an effort to approach the problem under study with the nature of the law that is real and in accordance with the reality that lives in society. While the nature of this research is descriptive giving an overview of a complete, detailed, and clear reality of the legal protection of a criminal offender in Class IIB Siak Sri Indrapura Detention House. From the results of the research and discussion it can be concluded that the first: protection of rights for children in the Class IIB Detention Center of Siak Sri Indrapura is that there are still children placed in detention centers or state detention centers, in the implementation of children's rights combined with adult prisoners; secondly, the constraints encountered in protecting the rights of children in Class II B Prisoners of Siak Sri Indrapura are lack of facilities and infrastructure in Class IIB Siak Sri Indrapura Detention Houses, no motivation from within the child, lack of cooperation with relevant agencies; thirdly, efforts were made to overcome the obstacles in protecting the rights of children in the Class IIB Siak Sri Indrapura State Detention House, namely to place children in the LPKA, to provide guidance for children and to maximize collaboration with relevant agencies. Advice from the author, first: children should not be placed in detention centers should be in LPKA; second, giving children's rights; third, in the implementation of the granting of children's rights, it should be separated from adult prisoners.